REGRESI PROBIT BINER PADA FAKTOR-FAKTOR YANG MEMPENGARUHI KEEFEKTIFAN PEMBELAJARAN PADA MASA COVID-19 - Husnul Fadhillah; Fibri Rakhmawati; Rima Aprilia (Math Educa Journal, 2022)
Online learning or distance learning is learning that utilizes technology whose teaching materials are sent using an online system. This learning system is an implementation of distance education carried out to try to prevent the spread of COVID-19. This study was conducted to find out what factors affect the effectiveness of learning during the COVID-19 pandemic. The data used is primary data by distributing google forms to students who are respondents at the Faculty of Science and Technology UIN North Sumatra Medan with the response variable is the effectiveness of the online learning system where (1) for effective and (0) for less effective using the probit regression method binary. The predictor variables used were the use of learning strategies, accuracy in mastering behavior, learning curriculum, student motivation, technology literacy and learning evaluation. The amount of data collected is 400 respondents with the results of the study at a significance level of 0.05 that the factors that affect the effectiveness of learning during the COVID-19 pandemic are the use of learning strategies and literacy of technology with a classification accuracy of 91.75%.